Aging induced changes in ice nucleation activity of combustion aerosol as determined by near edge X-ray absorption fine structure (NEXAFS) spectroscopy. Issue 4 (19th March 2020) - Mahrt, Fabian; Alpert, Peter A.; Dou, Jing; Grönquist, Philippe; Arroyo, Pablo Corral; Ammann, Markus; Lohmann, Ulrike; Kanji, Zamin A.
Abstract : Soot particles aged in acidic aqueous solutions reveal significantly enhanced ice nucleating activity. Abstract : Fresh soot particles are generally hydrophobic, however, particle hydrophilicity can be increased through atmospheric aging processes. At present little is known on how particle chemical composition and hydrophilicity change upon atmospheric aging and associated uncertainties governing the ice cloud formation potential of soot. Here we sampled two propane flame soots referred to as brown and black soot, characterized as organic carbon rich and poor, respectively. We investigated how the ice nucleation activity of these particles changed through aging in water and aqueous acidic solutions, using a continuous flow diffusion chamber operated at cirrus cloud temperatures ( T ≤ 233 K). Single aggregates of both unaged and aged soot were chemically characterized by scanning transmission X-ray microscopy and near edge X-ray absorption fine structure (STXM/NEXAFS) measurements. Particle wettability was determined through water sorption measurements. Unaged black and brown soot particles exhibited significantly different ice nucleation activities. Our experiments revealed significantly enhanced ice nucleation activity of the aged soot particles compared to the fresh samples, lowering the required relative humidities at which ice formation can take place at T = 218 K by up to 15% with respect to water (ΔRHi ≈ 25%). We observed an enhanced water uptake capacity for the aged compared to the unaged samples, which was more pronounced for the black soot. From these measurements we concluded that there is a change in ice nucleation mechanism when aging brown soot. Comparison of the NEXAFS spectra of unaged soot samples revealed a unique spectral feature around 287.5 eV in the case of black soot that was absent for the brown soot, indicative of carbon with hydroxyl functionalities. Comparison of the NEXAFS spectra of unaged and aged soot particles indicates changes in organic functional groups, and the aged spectra were found to be largely similar across soot types, with the exception of the water aged brown soot. Overall, we conclude that atmospheric aging is important to representatively assess the ice cloud formation activity of soot particles.